The association of cleft lip and palate with cervical vertebral anomalies- a lateral cephalographic study - C, Ashwini; David, Maria Priscilla; Swamy, Akanksha Anantha; Joseph, Sarojini; Muthaiah, Mallika (International Journal of Dental Research, 2017)
Background: Cleft lip and palate is the most common major congenital craniofacial abnormality noted, which is 1 in 700 births. Although inheritance may play a role, cleft lip and palate is considered to be of multifactorial etiology, including chemical exposures, radiation, maternal hypoxia, teratogenic drugs, nutritional deficiencies, especially folic acid and cervical vertebral anomalies.Objective: To assess an association between cleft lip and palate and cervical vertebral anomalies.Methodology: The lateral cephalographs of 74 cleft lip and palate patients aged 6- 20yr were traced for cervical spine from C1- C4 on an acetate paper. Cervical vertebral anomalies were recorded and categorized into posterior arch deficiencies and fusion or both.Results: 12.16% of cleft lip and palate patients had cervical vertebral anomalies.Conclusion: The association between cleft lip and palate and cervical vertebral anomalies indicates that cervical vertebral anomalies may be implicated in the etiology of cleft lip and palate. Cervical vertebral anomalies can predispose to further disorders and identification of such anomalies mandates referral to the concerned specialist for appropriate management.